HOLISTIC REHABILITATION AFTER POLYTRAUMA; INTERDISCIPLINAY INTERVENTION TO ENHANCE PATIENT ENABLEMENT - Mohd Redzuan, Nor Shahizan (International Journal of Allied Health Sciences, 2021)
Rehabilitation is the process of development of a person to his or her fullest physical, psychological, social, educational, and vocational potential, by eliminating or compensating for any anatomic impairment, activity limitation, or environmental barrier. In contrast to classic medical therapeutics, which emphasize diagnosis and focused treatment directed against the pathologic process, rehabilitation directs treatment against the pathologic process but also applies multiple simultaneous interventions addressing both the cause and secondary effects of injury and illness thru biopsychosocial model. Holistic Rehabilitation includes assessment of the individual’s personal capacities, role performance, and life aspirations. In other words, rehabilitation is the process of transforming a person with functional limitations to a person with “maximal ability” through the application of medical treatment, therapy, and adaptive equipment.